PENYULUHAN DAN BIMBINGAN TENTANG KEARSIPAN DAN KORESPONDENSI BAGI PARA GURU PENDIDIKAN USIA DINI (PAUD) DUSUN KLANDUNGAN DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG - Diana Eka Poernamawati; Achmad Zaini (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
The research objective to know the role of innovation in mediating market orientation to increase competitive advantages of Small Busines Enterprises (SMEs). Directly, the influence of  market orientation to competitive advantages is significant, but indirectly through innovation,  the influence of  market orientation to competitive advantages is not significant. This result show that is in the condition of SMEs are not export directly to the foreign consumer and they depend to the middlemen they can not easily to make some decision in  innovation. All of the product they made had to appropriated to the middlemen needs and wants without their own innovation efford. The location of research in Malang Raya and the repondend are SME’s with the export goal.